Draft Genome Sequence of Xylella fastidiosa Pear Leaf Scorch Strain in Taiwan - Su, C.-C. (American Society for Microbiology, 2014)
The draft genome sequence of Xylella fastidiosa pear leaf scorch strain PLS229, isolated from the pear cultivar Hengshan (Pyrus pyrifolia) in Taiwan, is reported here. The bacterium has a genome size of 2,733,013 bp, with a G+C content of 53.1%. The PLS229 genome was annotated and has 3,259 open reading frames and 50 RNA genes.